De las ciencias a la vida o sobre la productividad en la Ciénaga de Ayapel y su praccis (2015)
The praccis teaching’s strategy looks for, to translate dialogically, something strange, something from the world of science, into an approaching or perhaps something of his self, in the world of life. The scientist facts in this case, the strange thing, are the results of research on productivity in Ayapel´s swamp, Colombia, which is mediated by the praccis teaching strategy, in order to come closer to the people, who live in the same location, to facilitate the movement of knowledge. This research is made up of four parts: a first rigorously exposition of how productivity in Ayapel´s swamp is; a second which describes the praccis strategy; third which explains how to build the teaching strategy with knowledge from the marsh productivity and fourth, showing how the strategy was implemented and the results were that the semantic fields and their relationship with the links of the strategy praccis were attractive to residents of Ayapel.